KARAKTERISTIK KIMIA PRODUK SUSU FERMENTASI “KEFIR” BERANTIOKSIDAN SELAMA PENYIMPANAN - N. L. S. N., Ariani; Miwada, I N. S.; Lindawati, S. A (Jurnal Peternakan Tropika; Vol 4 No 2 (2016), 2016)
This research was conducted with the aim of evaluating the chemical characteristics of the fermented milk kefir and potential as antioxidants from purple sweet potato during storage and determine the retention time of how many days are still qualify as fermented milk products. Research method using a Completely Randomized Design (CRD) simple pattern with 5 treatments (T0 = 0 days; T1 = 1 day; T3 = 3 days; T5 = 5 days and T7 = 7 days) and do repetitions of each three times. Research fermented milk kefir each potentially antioxidant use purple yam with a concentration of 4%. Variable observed that the ash content, protein content, fat content, moisture content and water activity. The results showed that kefir purple yam on storage time T0-T7 was not significant (P>0,05) on water content and water activity, while at variable levels of protein in the treatment T5 significant (P<0,05) against the storage time T0-T3 with the highest storage time at T5 is 4,860%, levels of lactose at T5 treatment significantly (P<0,05) against the storage time T0-T3 with storage time high of T5 is 6,220% and ash content of the storage time at T5 effect significantly (P <0.05) against the long storage time T0 with the highest storage at T5 is 1,000%.The conclusions of this study is the shelf life of the product kefir purple yam storage for up to 5 days (T5) gives the best results with niali protein content of 4,86%, 6,22% lactose content, and ash content of 1,00%.
Keywords: kefir, purple sweet potato, long stroge, chemistry